Spinal Subarachnoid Hemorrhage Secondary to Rupture of an Isolated Radicular Artery Aneurysm - Marovic, Paul; Thani, Nova; Lu, Steven; Bala, Arul (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Aneurysmal subarachnoid hemorrhage (aSAH) of spinal origin is an uncommon entity and comprises less than 1% of all aSAH. The paucity of clinical cases creates challenges to its diagnosis and management. We present the case of a 58-year-old male, who presented with a spinal subarachnoid hemorrhage secondary to a de novo spinal radicular artery aneurysm. Spinal subarachnoid hemorrhages typically occur secondary to arteriovenous malformations or arterial wall weakness seen in collagen vascular disease. Fewer than 20 cases of isolated spinal arterial aneurysms have been published. SAHs of spinal origin are exceedingly rare and thus a high index of suspicion is required for an accurate and timely diagnosis.
Keywords: subarachnoid hemorrhage; spinal radicular artery; aneurysm